Method for enhancing mechanical strength of flexible perovskite solar cell interface based on PEDOT: PSS
By using imidazole bromine small molecules as interface linkers in flexible perovskite solar cells, the interface binding force between PEDOT:PSS and the perovskite active layer is improved, and the problem of interface fall off during bending strain is solved, which significantly improves the device stability and durability.
Patent Information
- Application Number
- CN202411528280.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
When flexible perovskite solar cells are bending and strained, PEDOT: The bonding force between the interface between the PSS and the perovskite active layer is poor, resulting in the falloff and fracture of the active layer, affecting the operating stability and service life of the device.
Imidazole bromine small molecules are used as interface linking agents to enhance interface binding force by having strong interaction with PEDOT:PSS and perovskites, and design methods to quantify interface binding force to optimize the preparation process of interface connection layer.
The binding force between perovskite and PEDOT:PSS interface is significantly improved, ensuring the operating stability and mechanical durability of flexible perovskite solar cells under different angle bending cycle conditions, and extending the service life of the device.
Smart Images

Figure CN119451518A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of flexible photovoltaic cells, and specifically is a method for enhancing the mechanical strength of the interface of a PEDOT:PSS-based flexible perovskite solar cell. Background Art
[0002] The energy supply system of aerospace equipment usually uses high energy-to-mass ratio energy to reduce the excessive energy consumption caused by launch. For example, the energy system carried by the Shenzhou XII manned spacecraft launched by my country in 2021 is a flexible solar wing panel and energy storage lithium battery. The solar wing panel converts the collected light energy into electrical energy, which is then stored by the energy storage battery. It is reported that the power density of the solar wing panel power supply surface equipped with the Tianhe core module is about 138.5W / m 2 This performance is far inferior to the surface power density of terrestrial crystalline silicon solar cells. This is because the power supply batteries for aviation equipment sacrifice a certain degree of output power in order to reduce weight. In recent years, the third generation of new photovoltaic solar cells has been booming. Among them, the photoelectric conversion efficiency of perovskite solar cells has increased to the same level as that of crystalline silicon solar cells in just ten years. The surface power density of large-area perovskite solar cells prepared in the laboratory has reached 228.6W / m 2 , and because the perovskite active layer of perovskite solar cells has the advantage of flexibility compared to the silicon light-absorbing layer, it is expected to replace the existing aerospace equipment energy supply batteries. However, the energy supply system of aerospace equipment not only needs to have higher photoelectric conversion efficiency and high surface power density, but also needs to have a certain degree of operational stability. For example, during the launch, orbital operation and landing of an aircraft, its energy supply system will experience severe vibration and bending strain. After restoring stability, the solar cell needs to still have a certain photoelectric conversion efficiency.
[0003] Flexible perovskite solar cells and flexible stacked solar cells based on perovskite active layers mostly use PEDOT:PSS as electrodes or hole transport layers, and PEDOT:PSS is in direct contact with the perovskite active layer. Therefore, the photovoltaic performance of solar cells is related to the photoelectric properties and surface characteristics of the PEDOT:PSS film. At present, a series of studies have been carried out in the field on PEDOT:PSS films, including the conductivity, light transmittance and pH of PEDOT:PSS films. However, the surface of high-performance PEDOT:PSS films is usually hydrophobic, which leads to poor interfacial contact between the PEDOT:PSS film and the hydrophilic perovskite active layer deposited on its upper surface. To address this problem, Tanushree Majhi et al. published a method for improving interfacial contact by plasma treatment of PEDOT:PSS surface in "Insight into Controlled Surface Passivation of PEDOT:PSS for Defect Density Modulation and Efficient Charge Transport for Perovskite Solar Cells"; Zhiyin Niu et al. published a method for modifying the surface properties of PEDOT:PSS films by toluene vapor and ethylene glycol washing in "Manipulation of PEDOT:PSS with Polar and Nonpolar Solvent Post-treatment for Efficient Inverted Perovskite Solar Cells"; In-Seong Hwang et al. published a study on the surface modification of PEDOT:PSS by tannic acid in "Post-Treatment of Tannic Acid for Thermally Stable PEDOT:PSS Film" to improve film performance. However, these studies usually focus on the lower PEDOT:PSS material itself, without considering the chemical properties of PEDOT:PSS and the perovskite active layer. The two layers of material are still in physical contact, which means that the interface bonding between the two layers is poor. Therefore, when flexible devices based on PEDOT:PSS substrate materials experience bending strain, the upper active layer will fall off and break due to interface bonding, hindering the application of flexible solar cells.
[0004] Considering that the application targets of flexible perovskite solar cells are wearable devices and aircraft power supply systems, they face extremely high bending requirements, and the desorption problem at the interface between PEDOT:PSS and the active layer greatly reduces the expected service life of photovoltaic devices. Currently, interface analysis technology is usually used to characterize the interface morphology and active layer crystal quality. However, there is no effective quantitative method or improvement method for the bonding strength of the interface. Summary of the invention
[0005] The present invention proposes a method for improving the mechanical strength of the interface of PEDOT:PSS-based flexible perovskite solar cells (FPSCs) by using imidazole bromide small molecules as an interface connector. This method utilizes the strong interaction between imidazole bromide and both perovskite and PEDOT:PSS to improve the interface bonding strength between perovskite and PEDOT:PSS, ensuring that the ultra-flexible perovskite device has a certain operating stability under bending and cycling conditions at different angles. In addition, we designed a method for quantifying the interface bonding strength, which can effectively compare the bonding strength between the interfaces before and after modification, and optimize the preparation process of the interface connection layer through feedback from the interface bonding strength test results.
[0006] The technical solution of the present invention:
[0007] A method for enhancing the mechanical strength of the interface of a PEDOT:PSS flexible perovskite solar cell, specifically a method for enhancing the interface bonding strength using imidazole bromide as an interface connector, and the specific steps are as follows:
[0008] The PEDOT:PSS flexible perovskite solar cell is mainly composed of an ultra-flexible substrate (PET), an ultra-flexible transparent electrode (PEDOT:PSS), an interface connector imidazolium bromide layer (ImBr), a perovskite light absorbing layer (Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03)3), electron transport layer (PCBM), hole blocking layer (BCP), metal electrode (Ag); except for the interface connector, the preparation methods of other functional layers and active layers refer to the paper "Al2O3nanoparticles as surface modifier enables deposition of high quality perovskite films for ultra-flexible photovoltaics" published by Zhiyong Wang et al. in Advanced Powder Materials. The IMBr connector is prepared by dissolving imidazole bromide molecules in anhydrous methanol and stirring to form a uniform solution. The prepared connector can be stored for a long time. The IMBr connecting layer is prepared by dropping the IMBr connector on the surface of PEDOT:PSS, standing for several seconds to form a stable connection, and curing by spin coating and annealing process. The final interface connection layer is connected to the PEDOT:PSS terminal molecules through a single layer of molecules. The IMBr thickness is related to the connector concentration and the standing time. In actual use, the corresponding preparation parameters need to be optimized according to the interface bonding force and device performance.
[0009] The spin coating and annealing curing process specifically includes spin coating at 2000-5000 rpm for 40 seconds and annealing at 100-140° C. for 5 minutes.
[0010] Wherein, the concentration of the IMBr interface connector solution is 0.5-3 mg / mL.
[0011] Among them, the standing time is 1-6s.
[0012] The ultra-flexible substrate uses an ultra-thin (thickness = 10μm) highly transparent PET film as the supporting material of the battery. The ultra-thin bottom substrate can reduce the tensile stress on the interface of UF-PSCs when bending, and improve the bending resistance of the device. In addition, the UV-O3 treatment makes it have better surface wettability, so that the PEDOT:PSS electrode layer can be fixed on the substrate.
[0013] The ultra-flexible transparent electrode PEDOT:PSS was prepared on a substrate by a solution method, and the imidazolium bromide linker was anchored to the PEDOT:PSS electrode layer by spin coating and incubation processes. Subsequently, the perovskite active layer was prepared on the exposed imidazolium bromide surface and fixed.
[0014] The interface bonding force is quantified by mechanically stretching the device structure into two parts. Specifically, the bottom electrode and perovskite active layer of UF-PSCs are prepared on a glass substrate to form an interface stretch bottom structure, and then another piece of the same glass with epoxy resin glue is buckled on the top surface of the perovskite active layer to form an interface stretch top structure. A fixture corresponding to the size of the device structure is designed and the interface stretch test is performed using a mechanical stretch test bench.
[0015] Beneficial effects of the present invention:
[0016] 1. The present invention manufactures an imidazolium bromide interface connection layer, anchors the positive charge N of the imidazolium ion with the PSS- on the PEDOT:PSS surface, and coordinates the lone pair of electrons N in the imidazolium ion structure with the terminal Pb ions of the perovskite active layer to form a strong chemical contact, thereby effectively optimizing the interface contact between the perovskite active layer and the substrate of the PEDOT:PSS-based flexible perovskite solar cell.
[0017] 2. The present invention can achieve precise optimization of the thin film preparation process by quantifying the bonding force of the active layer interface of the ultra-flexible perovskite solar cell and determining the mechanical strength of the interface, thereby greatly improving the effectiveness of interface strengthening.
[0018] 3. The imidazole bromide interface connection layer used in the present invention uses a simple spin coating process with strong repeatability, and is suitable for the interface bonding force optimization scheme of various thin film devices. It can also improve the tolerance of flexible perovskite solar cells under small-angle bending conditions by enhancing the interface mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the structure of an ultra-flexible perovskite solar cell;
[0020] Figure 2 This is the standard light intensity photocurrent-voltage curve of the ultra-flexible perovskite solar cell;
[0021] Figure 3 It is the interface tensile load-tensile stroke curve of ultra-flexible perovskite solar cells before and after the imidazolium bromide connecting layer is used;
[0022] Figure 4 This is the PCE-cycle number curve of the 0.5mm radius cyclic bending test of the ultra-flexible perovskite solar cell. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0024] Example
[0025] Preparation of ultra-flexible perovskite solar cells:
[0026] Step (1) Cleaning and attaching of ultra-flexible substrate: The PET substrate was cleaned with detergent, deionized water, anhydrous ethanol, and isopropanol in sequence and ultrasonicated for 15 minutes, and then treated with ultraviolet ozone for 20 minutes. Polydimethylsiloxane (PDMS) was mixed with a curing agent (mass ratio of 10:1) and diluted with 2 times the mass of n-hexane, and spin-coated on a clean glass substrate at a speed of 2000 rpm for 30 seconds, and then annealed at 100°C for 5 minutes. The PET film was attached to the glass / PDMS substrate, and after cooling, the excess PET film was cut and transferred to a vacuum chamber to remove the air between the PET and PDMS.
[0027] Step (2) Preparation of ultra-flexible transparent electrode: After filtering PEDOT:PSS, dimethyl sulfoxide (DMSO) and fluorocarbon surfactant (FS-300) were added in a volume ratio of (1000:50:5). After shaking, PEDOT:PSS was spin-coated on a PET substrate at a speed of 1000 rpm for 40 seconds, and then annealed at 120°C for 30 minutes. After cooling, the methanol solution was added dropwise to the surface of PEDOT:PSS and spin-coated on PEDOT:PSS at a speed of 4000 rpm for 30 seconds, and then annealed at 120°C for 5 minutes. After cooling, conductive silver glue (Ag-3702) was scraped on one side of the PEDOT:PSS electrode layer with a scraper to expose the bottom electrode.
[0028] Step (3) Preparation of the interface connection layer: 1.5 mg of imidazole bromide was dissolved in methanol, and the methanol solution of imidazole bromide was added dropwise onto the PEDOT:PSS electrode, and then allowed to stand for 3 seconds to ensure that the imidazole bromide was connected to the substrate PSS, and then the excess imidazole bromide solution was removed by spin coating at 4000 rpm for 40 seconds, and then annealed at 120°C for 5 minutes to remove the methanol solvent.
[0029] Step (4) Preparation of perovskite light absorbing layer: ① Preparation of perovskite precursor solution: Add 0.077M CsI, 0.143MMABr, 1.3M FAI, and 1.62M PbI2 to a mixed solution of DMF and DMSO (800μL DMF+200μL DMSO). The precursor solution was stirred at 60°C for 1h and filtered with a 0.22μm polytetrafluoroethylene membrane before use. ② Preparation of perovskite film: Add the components Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03)3 perovskite precursor solution was added dropwise onto the PEDOT:PSS substrate and spin coated at 4000 rpm for 30 seconds. Within 5 seconds before the end of the program, 200 μL of ethyl acetate was quickly added onto the liquid film. After the spin coating was completed, the device was quickly transferred to a 70°C heating table for annealing for 1 minute, and then transferred to a 100°C heating table for annealing for 15 minutes to completely transform it into a black phase.
[0030] Step (5) Preparation of PCBM electron transport layer: 20 mg PCBM was added to 1 mL chlorobenzene solution and ultrasonicated for 10 min. After it was completely dissolved, it was filtered using a 0.22 μm polytetrafluoroethylene membrane. The filtered PCBM solution was spin-coated on the perovskite film at a speed of 1500 rpm for 30 seconds and annealed at 60° C. for 5 min.
[0031] Step (6) Preparation of BCP hole barrier layer: 0.5 mg BCP powder was added to 1 mL isopropanol solution, ultrasonicated for 10 min, and then shaken for 6 h to form a supersaturated solution, which was filtered using a 0.22 μm polytetrafluoroethylene membrane. The filtered BCP solution was spin-coated on the PCBM film at a speed of 5000 rpm for 30 seconds and annealed at 60° C. for 5 min.
[0032] Step (7) Preparation of metal counter electrode: Place the multilayer film prepared in the above step into a mask plate and place it in a vacuum deposition chamber. -4 After Pa, first The Ag electrode is evaporated to Then increase the rate to Ag was evaporated to a thickness of The device preparation is completed.
[0033] Table 1 Optimization of imidazole bromide linker concentration
[0034] 0.5mg / mL 1.0mg / mL 1.5 mg / mL 3mg / mL Binding force 182 N 223N 247N 165N
[0035] Table 2 Optimization of imidazole bromide linker standing time
[0036] 1s 2s 3s 6s Binding force 242 N 243N 340N 182N
[0037] Table 3 Optimization of spin coating process of imidazole bromide linker
[0038] 2000rpm 3000rpm 4000rpm 5000rpm PCE(%) 16.67 17.63 17.69 17.50
[0039] Table 4 Optimization of annealing process of imidazole bromide linker
[0040] 100℃ 110℃ 120℃ 140℃ PCE(%) 17.33 17.68 17.88 17.53
[0041] Comparative example: Ultra-flexible perovskite solar cells without interfacial connectors
[0042] The preparation method is basically the same as that in the embodiment, except that there is no step (3) of preparing the interface connection layer.
[0043] Preparation and testing of interface stretching devices.
[0044] Step (1) Preparation of bottom structure: The glass substrate was cleaned with detergent, deionized water, anhydrous ethanol, and isopropanol and ultrasonicated for 15 minutes. Then, the ultra-flexible transparent electrode PEDOT:PSS, the interface connection layer imidazole bromide, and the perovskite light absorption layer were prepared in sequence according to the preparation process of ultra-flexible perovskite solar cells.
[0045] Step (2) Preparation of protective layer: A protective layer was prepared using polymethyl methacrylate (PMMA), and then 15 mg of PMMA was dissolved in 1 mL of chlorobenzene solution, heated and stirred at 70° C. for 4 h until completely dissolved. The PMMA solution was then spin-coated on the perovskite film at a speed of 5000 rpm and annealed at 100° C. for 1 min to remove the solvent.
[0046] Step (3) Preparation of bonding layer and cover plate: Apply epoxy resin glue evenly on a clean glass plate, and then press the glue surface onto the PMMA protective layer so that the epoxy resin glue completely covers the contact surface, and then cure it under ultraviolet light for 1 minute.
[0047] Step (4) Interface stretching experiment and test: Place the upper and lower glass pieces of the prepared interface stretching device into the interface stretching fixture respectively, fix the glass substrate with screws, and then apply load by uniformly applying a stretching stroke (0.4 mm / min). When the interface stretching load limit is reached, the fracture occurs, and the fracture point load is recorded. The mechanical strength of the interface is determined by comparing the tensile fracture load values.
[0048] The schematic diagram of the device structure is as follows Figure 1 As shown, the prepared device was exposed to standard simulated sunlight AM1.5G (100mW / cm 2 ), use standard silicon cells (B5-520) to calibrate the light intensity, use Keithley2400 instrument to test, the current-voltage test results are as follows Figure 2 The specific test results are shown in Table 5.
[0049] Table 5 Specific test results of ultra-flexible perovskite solar cells
[0050]
[0051] V OC is the open circuit voltage, J SCis the short-circuit current, FF is the fill factor, and PCE is the photoelectric conversion efficiency. The results show that the imidazolium bromide connection layer, as an interface mechanical strengthening method, has no negative effect on the photoelectric conversion efficiency of the overall device, and has achieved a certain positive improvement, among which the device open circuit voltage increased (1.014 to 1.074) and the fill factor increased (65.86 to 68.56), proving the improvement effect of the interface contact.
[0052] Flexible perovskite solar cells with imidazolium bromide connection layer before and after the interface tensile load-stretching stroke curve Figure 3 As shown, compared with the comparative example, the interface bonding force between the perovskite active layer and the PEDOT:PSS substrate is greatly improved after the interface mechanical strengthening of the IMBr connecting layer in the embodiment, and the breaking load is increased from 123N to 340N, which undoubtedly improves the tolerance of flexible perovskite solar cells to bending strain.
[0053] In order to verify the effect of the IMBr interface connection layer on the mechanical durability of the device, the flexible perovskite solar cell was subjected to strain cycles with a bending radius of 0.5 mm, and the bending was stopped at 1 cycle, 10 cycles, 50 cycles, 100 cycles, 500 cycles, 1000 cycles, 2000 cycles, 5000 cycles and 10000 cycles to conduct photoelectric performance tests. The PCE-cycle number curve of the flexible perovskite solar cell 0.5 mm radius cyclic bending test is shown in Figure 2. Figure 4 As shown. After 1000 cycles of bending, significant changes occurred, indicating that the interface connection layer has a good performance on the stability of the device structure, reducing the risk of damage to the active layer, and after the bending cycle reaches 10,000 times, there is a significant difference. The embodiment greatly improves the mechanical durability of the PEDOT:PSS-based flexible perovskite solar cell through the interface bonding strengthened by the IMBr interface connection layer, and still maintains the initial photoelectric conversion efficiency of 82.4%.
[0054] As described above, for ordinary technicians in this field, various other corresponding structural changes and deformations can be made according to the technical solutions and technical concepts of the present invention, and all these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A method for enhancing the mechanical strength of the interface of a PEDOT:PSS-based flexible perovskite solar cell, wherein the PEDOT:PSS-based flexible perovskite solar cell is mainly composed of an ultra-flexible substrate, an ultra-flexible transparent electrode, a perovskite light-absorbing layer, an electron transport layer, a hole blocking layer and a metal electrode; characterized in that: The PEDOT:PSS-based flexible perovskite solar cell also includes an interface connector imidazole bromide layer, which is located between the ultra-flexible transparent electrode and the perovskite light-absorbing layer; The method for improving the interfacial bonding strength using imidazole bromide as an interfacial connector is as follows: (1) preparing an ultra-flexible substrate and an ultra-flexible transparent electrode in sequence; (2) preparing an imidazolium bromide interface connector layer: dissolving imidazolium bromide molecules in anhydrous methanol and stirring to form a uniform IMBr interface connector solution; The IMBr interface connector solution is drop-coated on the surface of the ultra-flexible transparent electrode, left to stand for a few seconds to form a stable connection, and then solidified by spin coating and annealing process to form an interface connector imidazolium bromide layer connected to the ultra-flexible transparent electrode terminal molecules through a single layer of molecules; (3) Finally, the perovskite light absorbing layer, electron transport layer, hole blocking layer and metal electrode are prepared in sequence.
2. The method for enhancing the mechanical strength of the interface of a PEDOT:PSS flexible perovskite solar cell according to claim 1, characterized in that: In step (2), the spin coating and annealing process curing is specifically 2000-5000 rpm spin coating for 40 seconds, and 100-140° C. annealing for 5 minutes.
3. The method for enhancing the mechanical strength of the interface of a PEDOT:PSS flexible perovskite solar cell according to claim 1, characterized in that: In step (2), the concentration of the IMBr interface connector solution is 0.5-3 mg / mL.
4. The method for enhancing the mechanical strength of the interface of a PEDOT:PSS-based flexible perovskite solar cell according to claim 1, characterized in that: In step (2), the standing time is 1-6s.